Systematic and Population Genetics of Bornean Limnonectes kuhlii Complex (Anura: Dicroglossidae) - Najmi, Naim (Universiti Malaysia Sarawak (UNIMAS), 2020)
Limnonectes kuhlii is notorious for its species complex where closely related species have analogous appearances to the point that it is frequently laborious to differentiate between them. The aim of this study is to elucidate the relationship among lineages of L. kuhlii in Borneo determined by shape variation and genetic variation. Ergo, all individuals conferred or subsumed as Bornean L. kuhlii is treated as conspecific or putative species as a null hypothesis. For morphological assessment, 235 specimens were measured, and 189 DNA sequences were utilized in molecular assessment. Samples accumulated across Malaysian Borneo, covering Sarawak and Sabah. In morphological assessment, the analyses congruently showed important variations in head region dimensions are affected by sexuality while limb regions dimensions are affected by locality. The sexual size dimorphism could be related to feeding ability, male-male combative behavioural and sexual selection. Forelimb and hindlimb shape are varied across the geographical region. Sabah population has longer hindlimb relative to body length than Sarawak population. Shape variation in limb dimension counterpart to the density and size of tubercles at the hindlimb and present of the nuptial pad in males where these characters are repeatedly worked by previous studies to describe recently distinct species from the ‘true’ Javan L. kuhlii. In molecular assessment, ten population lineages are identified as the members of L. kuhlii complex in Borneo with six prospective candidate species. Two major clades are recovered but there is no evidence of the geographical separation between major clades nor depicting geographical proximate cluster. Nonetheless, the geographical structuring is more prominent within population lineages. Tectonostratigraphic zone of Borneo determines the genetic variation among and within the lineages of Bornean L. kuhlii. Lupar Line, Rajang River and some highlands acts as genetic barriers where the population lineages are genetically distinct from their adjacent geographical group. Lupar Line acts as the genetic boundary showed species that distributed in the west Sarawak does not exist in the east Sarawak conversely species that dispersed across the east Sarawak does not exist in the region of the west. However, several species of both areas might co-exist within the boundary as sympatric. Understanding of the species evolutionary history provides insight into the geological and tectonic event of the Borneo. Immediate conservative action is desperately required to diagnose and to name the candidate species of Limnonectes especially in Sabah and eastern Sarawak.